Giant abdominal cerebrospinal fluid pseudo cyst: A case report - Amal Mojahid; Nadia El Mahi; Hamid Ziani; Siham Nasri; Imane Kamaoui; Imane Skiker (Radiology Case Reports)
The cerebrospinal fluid pseudocyst is an uncommon complication of the ventriculoperitoneal shunt used to treat hydrocephalus. It manifests as the accumulation of fluid around the distal end of the catheter, surrounded by a fibrous wall lacking epithelium. Its exact origin remains uncertain. We present here a case of a large peritoneal pseudocyst, filling the abdominal cavity and exerting pressure on adjacent structures. Management involved external drainage followed by the implantation of a new ventriculo-atrial shunt.